Australian psychologists' perceptions and experiences of client threats - Hyde, Penny (2014)
There is empirical evidence that workplace violence is increasing, particularly in settings where health care professionals such as psychologists are employed, and often these incidents are perpetrated by clients. Given that client violence can have wide ranging and serious consequences, it is not surprising that researchers are focussing on this issue. One notable finding is that psychologists feel that they do not have the training or confidence to manage the violent behaviour of clients. A review of the relevant literature was undertaken to determine why psychologists feel ill prepared for such incidents. Whilst there is a wide range of definitions of client violence, it appears that many of the professionals’ concerns about various forms of client behaviour go beyond these definitions of violence. There is an array of client behaviours that make professionals feel their wellbeing is at risk which fall outside the general definition of violence. Consequently, the term client threats may be more appropriate. There is no research in which psychologists were directly asked what client interactions they perceived as putting their wellbeing at risk and, without this information, professional advice to them may not be effective. The purpose of this research project was to determine psychologists’ experiences and perceptions of client threats. Stage 1 included interviews with 45 psychologists which indicated that their experiences and perceptions of client threats could be best conceptualised by developing a preliminary theory of client threat. In stage 2 a Delphi approach, with a panel of experts, helped formulate a modified Client Threat Theory that proposes a three phase model outlining the process through which psychologists experience these threats. This theory begins with a client behaviour being observed and conceptualised as a threat (activation phase), then influential factors are assessed (risk assessment), and lastly a management plan is formulated and applied in response to the threat (execution phase). This research project also provides a detailed understanding of how the participating psychologists experienced client threats. It was discovered that threatening experiences were triggered by more than violent client behaviours and that a term broader than violence was needed to encompass these experiences. The types of threats reportedly experienced by participants were physical, sexual, verbal, psychological, reputational, and financial in nature. Participants also reported feeling threatened when they perceived that a client behaved in a threatening manner towards people known to them, such as colleagues and family members. This provides a basis from which future researchers could develop a comprehensive definition and theory of client threat, along with efficient and effective tools to reduce its occurrence and deal with it more effectively